2021
DOI: 10.1088/1742-6596/1714/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Investigating impact of Influential Factors of Online Advertisement on Youth’s Online Buying Behavior: A Predictive Model

Abstract: The impact of online advertisement on consumers which motivates them to do online shopping encouraged the researchers, managers, and policymakers to analyse this impact. In any case, because of its perplexing nature, this wonder is still in its early stages in many nations and should be given more consideration. Using advanced statistical tools (AST), the main aim of the present study is to identify the factors that influence the youth to indulge in online shopping in Jaipur, India. Information were gathered f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The study also found other factors that influence online consumers, including low price, discount, feedback from previous customers, and product quality. [14], [15], [16], discuss the impact of advertisement, website design, psychological factors on consumer behaviour.…”
Section: Post-purchase Behaviourmentioning
confidence: 99%
“…The study also found other factors that influence online consumers, including low price, discount, feedback from previous customers, and product quality. [14], [15], [16], discuss the impact of advertisement, website design, psychological factors on consumer behaviour.…”
Section: Post-purchase Behaviourmentioning
confidence: 99%